Beer places : the microgeographies of craft beer - Harvey, Daina Cheyenne; Jones, Ellis, 1970-; Chapman, Nathaniel G. (Food and foodways (Fayetteville, Ark.), 2023)
"Beer Places is both a road map for craft beer and an academic analysis of craft beer's ties to place. Collected into sections that address authenticity and revitalization, politics and economics, and collectivity and collaboration, this volume blends new research with a series of "postcards": informal conversations and first-person dispatches from the field that transport readers to the spots where pints are shared and networks forged"--